A retrospective study to assess the influence of anaesthetic type on incomplete excision rate for non-melanoma skin cancers - Page, Daniel W.; Watter, Henry; Ng, Guat Shi; Silva, Munasinghe (International Surgery Journal, 2021)
Background: Australia has the highest incidence of non-melanoma skin cancers (NMSC) in the world estimated to be 2448/100,000 population with the state of Queensland carrying the highest burden of disease. Surgical excision is the primary treatment and makes up a large proportion of general surgical lists in regional Queensland where they are typically removed using either local anaesthetic (LA) alone, local anaesthetic and sedation (LAS), or general anaesthesia (GA). There is little in the literature to suggest if anaesthetic type effects the rate of incomplete excision. The purpose of this study is to establish if anaesthetic type impacts the rate of incomplete excision of NMSC. Methods: A retrospective audit was performed, incorporating a total of 194 squamous and basal cell carcinoma lesions excised between October 2019 and October 2020 at two hospitals in regional Queensland, Australia. Data was recorded for the type of anaesthetic used and the histopathology of the lesions including type of lesion and clearance of microscopic margins. Results: Of the 194 excised lesions 39 of them had involved margins (20.1%). The rate of involved margins under LA, GA and LAS were found to be 19.79, 18.52 and 22.73% respectively. When comparing these modalities with each other: LA vs. GA, LAS vs. GA and LA vs. LAS no significant difference was found in the rate of incomplete excision of NMSC with p values (<0.05) of 1, 0.62 and 0.82 respectively. Conclusions: Modality of anaesthetic used for excision of NMSC does not affect the outcome of incomplete excision of NMSC.